Malaysian rural secondary school students' attitudes towards learning English as a second language - Zulkefly Balan, Farah; Mohamed Razali, Abu Bakar (Faculty of Education, Eskisehir Osmangazi University, 2019)
Students' attitudes towards learning English as a second language is not a new issue, yet much is to be known about the factors that actually affect the students' attitudes, especially those who live in rural areas that are known to have poor perceptions towards as well as poor performance in learning the English language as compared to Malaysian students who live in urban areas. Using Spolsky's (1989) Model of Second Language Learning and Gardner's (1985) Second Language Acquisition Theory, this study examines rural Malaysian students' attitudes towards learning English as a second language. The main objective is to investigate the individual elements or factors influencing rural secondary school students' attitude towards learning the English language. By employing a case study approach, four students from two different grade levels in a rural secondary school were purposely selected and individually interviewed and observed in their learning environments. The data were analysed using within and cross case analyses as well as thematic analysis, in which the authors read and annotated interview transcripts, identified themes, developed a coding scheme and coded the data. The findings suggest that there were two most significant factors influencing the students' attitudes towards the learning of English; i) lessons not catered to students' proficiency levels and interests, and ii) students' individual reactions to negative and positive experiences.